The incidence of breast cancer in population of young women from Podkarpackie province in 2002–2011 - Aneta U. Radziszewska; Bożenna Karczmarek-Borowska; Monika Grądalska-Lampart; Agata A. Filip (Contemporary Oncology)
Introduction : Breast cancer (BC) in young women of Podkarpackie province accounts for approximately 11.0% of all diagnosed breast tumors. Aim of the study was to assess the trends in incidence of BC among women younger than 44 from Podkarpackie in the years 2002–2011. Material and methods: 614 cases of malignant BC and 26 cases of cancer in situ were analyzed. The crude and the standardized incidence ratios were estimated; the percentage of histopathologically confirmed cancer cases and the percentage share of registered malignant breast tumors were calculated. The analysis of incidence in individual counties was also presented, as well as the stages of clinical advancement at diagnosis and the methods of treatment. Results : The number of registered cases at 2011 was 73, and it was 37.7% higher as compared to 2002. During the period analyzed, the increase in the crude and the standardized cancer incidence ratios was observed. The percentage share of BC in the examined group increased of 5.4% in 2011. Significant variation in incidence among different counties was observed. The incidence ratios ranged from 65.8 to 93.1/100 000. BC in young women most commonly was diagnosed as locally advanced and over 70% of patients were radically treated. Conclusions : Even though the progress in diagnostics and treatment has been made, BC in young women is diagnosed later than it should be and at considerably advanced stage. It is relevant to propagate the knowledge among women and health professionals to emphasize that BC may affect young women.